2012
DOI: 10.1093/mnras/sts327
|View full text |Cite
|
Sign up to set email alerts
|

Vertical density waves in the Milky Way disc induced by the Sagittarius dwarf galaxy

Abstract: Recently, Widrow and collaborators announced the discovery of vertical density waves in the Milky Way disk. Here we investigate a scenario where these waves were induced by the Sagittarius dwarf galaxy as it plunged through the Galaxy. Using numerical simulations, we find that the the Sagittarius impact produces North-South asymmetries and vertical wave-like behavior that qualitatively agrees with what is observed. The extent to which vertical modes can radially penetrate into the disc, as well as their amplit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
246
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(291 citation statements)
references
References 27 publications
44
246
1
Order By: Relevance
“…The validity of this diagnostic was confirmed with N-body simulations (Gómez et al 2012b) and found to be consistent with structure in the SEGUE G-dwarf sample (Gómez et al 2012a). Gómez et al (2013) showed that just such a disturbance from the Sagittarius dwarf galaxy can explain the recent discovery of vertical waves near the Sun in SEGUE (Widrow et al 2012) and RAVE (Williams et al 2013). …”
Section: Constraining Recent Merger Eventsmentioning
confidence: 64%
See 1 more Smart Citation
“…The validity of this diagnostic was confirmed with N-body simulations (Gómez et al 2012b) and found to be consistent with structure in the SEGUE G-dwarf sample (Gómez et al 2012a). Gómez et al (2013) showed that just such a disturbance from the Sagittarius dwarf galaxy can explain the recent discovery of vertical waves near the Sun in SEGUE (Widrow et al 2012) and RAVE (Williams et al 2013). …”
Section: Constraining Recent Merger Eventsmentioning
confidence: 64%
“…Evidence for merger encounters can be found in the phasespace structure of Milky Way disc stars (e.g., Gómez et al 2013Gómez et al , 2012bMinchev et al 2009). …”
Section: The Galactic Thick Discmentioning
confidence: 99%
“…Evidence for satellite-disk encounters can be found in structure in the phase-space of MW disk stars (e.g., Minchev et al 2009;Gómez et al 2013Gómez et al , 2012c, which can last for as long as ∼4 Gyr (Gómez et al 2012a). …”
Section: Thick-disk Formation Scenariosmentioning
confidence: 99%
“…Velocity and number density perturbations normal to the Galactic midplane can result from satellite-disk interactions (Widrow et al 2012;Gómez et al 2013;Widrow et al 2014). Gómez et al (2013), for example, used N-body experiments to show that a Sagittarius-like dwarf with a mass of 10 10.5 − 10 11 M⊙ could produce density perturbations of the same amplitude as was seen in Widrow et al (2012) and Yanny & Gardner (2013).…”
Section: Introductionmentioning
confidence: 99%